A short history of small machines - De Mol, Liesbeth; Bullynck, Maarten (The Turing Centenary Conference CiE 2012: How the World Computes, 2012)
One of the most famous results of Alan M. Turing is the so-called universal Tur- ing machine (UTM). Its in uence on (theoretical) computer science can hardly be overestimated. The operations of this machine are of a most elementary na- ture but nonetheless considered to capture all the (human) processes that can be carried out in computing a number. This kind of elementary machine ts into a tradition of `logical minimalism' that looks for simplest sets of operations or axioms. It is part of the more general research programme into the foundations of mathematics and logic that was carried out in the beginning of the 20th cen- tury. In the 1940s and 1950s, however, this tradition was rede ned in the context of `computer science' when computer engineers, logicians and mathematicians re-considered the problem of small(est) and/or simple(st) machines in the con- text of actual engineering practices. This paper looks into this early history of research on small symbolic and physical machines and tie it to this older tradi- tion of logical minimalism. Focus will be on how the transition and translation of symbolic machines into real computers integrates minimalist philosophies as parts of more complex computer design strategies. This contextualizes Turing's machines at the turn from logic to machines.